Observations of a Coastal Population of Huemul, Hippocamelus Bisulcus (Artiodactyla: Cervidae) in Riesco Island, Magallanes Region, Chile: A Conservation Opportunity - Moreira-Arce, D (De Gruyter Open Ltd, 2021)
We document the presence of a huemul population on Cabo León, Riesco Island, Chilean Patagonia 15 years after its first assessment, providing ecological insights for this southernmost coastal population. During Austral spring 2018 we recorded indirect signs of huemul presence and five individuals including one yearling across 35 km of trails, estimating a density of 2.3 ind/km2. Records were distributed in dense secondary forest, at low elevations and slopes. These observations suggest the presence of a breeding population, favored by the establishment of a private reserve and the reduction of livestock, along with the recently established Kawésqar National Park. © 2021 Walter de Gruyter GmbH, Berlin/Boston 2021.
Keywords: huemul abundance; huemul ecology; Parque Nacional Kawesqar; Patagonia